2011
DOI: 10.1007/s00436-011-2448-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes of adult Schistosoma mansoni worms recovered from C57BL/6 mice passively immunized with normal and vaccinated rabbit sera in vivo

Abstract: The purpose of the study is to explore the role of humoral immunity against Schistosoma mansoni infection in C57BL/6 mice using highly resistant rabbits that had been exposed to three separate immunizations with ultraviolet (UV)-irradiated cercariae (8,000 attenuated cercariae/rabbit in each immunization), and their sera were tested for their ability to transfer protection against S. mansoni challenge. The present study showed the reduction in challenge worm burden had reached 32.76-43.64% when compared with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…This result in comparing with that results obtained by Abdeen et al (2011). As RA vaccine generate high level of protection against subsequent challenge is not acceptable for use in human, reaching to vaccine depends on attenuated cercariae with indirect way as further target.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result in comparing with that results obtained by Abdeen et al (2011). As RA vaccine generate high level of protection against subsequent challenge is not acceptable for use in human, reaching to vaccine depends on attenuated cercariae with indirect way as further target.…”
Section: Discussionsupporting
confidence: 82%
“…The data generated from our recent study (Abdeen et al 2011) suggest that high levels of antibodies were developed in the vaccinated rabbit sera after multiple exposures to UVattenuated cercariae of S. mansoni; this might explain a passive transfer of protection from the infection and elimination of the worms. Therefore, as a continuation of our recent study, the present study aims to compare vaccine efficacy of single or multiple vaccination strategy, subcurative dose (20 mg/kg) of PZQ, and a combination of single vaccination with subcurative dose of PZQ on the surface topography of adult S. mansoni.…”
Section: Introductionmentioning
confidence: 93%
“…Complementary transmission electron microscopy studies have confirmed that the blebs pinch directly from the tegumental surface and are released into the extracellular environment ( Figure 2) [55,[57][58][59]. It has been suggested that blebbing is an attempt by helminths to replenish tegument that has been lost or damaged due to drug action [60] or humoral immune challenge [61]. Given the abundance of pumps such as P-glycoprotein 1 in the parasite EV membrane [47] it is possible that blebs sequester anthelmintics before their release; thus, reducing their effective local concentration in the parasite tissues.…”
Section: Are There Novel Ev Biogenesis Pathways In Helminths?mentioning
confidence: 91%
“…The data generated from Abdeen et al (2012) has suggested that high levels of antibodies were developed in the vaccinated rabbit sera after multiple exposures to UV-attenuated cercariae of S. mansoni, explaining a passive transfer of protection from the infection and elimination of the worms. Reda et al (2012) compared vaccine efficacy of a single or multiple vaccination strategy, subcurative dose (20 mg/kg) of praziquantel (PZQ), and a combination of single vaccination with subcurative dose of PZQ on the surface topography of adult S. mansoni.…”
Section: Introductionmentioning
confidence: 98%